SOCIAL IMPACTS OF THE COMING IMMIGRANTS ON THE NATIVE AMERICAN: A Study on James Fenimore Cooper’s The Prairie - . Suparman (Kajian Linguistik dan Sastra, 2007)
This literary research is primarily aimed at revealing the social impacts of modernizationon the traditional life as reflected in Cooper’s The Prairie. The study usesinterdisciplinary approach, which involves historical, cultural, and ecological approaches,including mimetic approach. The analysis shows that modernization doesnot only cause positive impacts but also stronger negative impacts. The negativeimpacts include human conflict, cultural conflict, imbalanced ecology, poverty, disharmony,social injustice of mixed marriage, greediness, kidnapping, and law breaking.The positive impacts include independence, adaptation, rationality, and efficiency.The problems that appear in the novel reflect the inner conflict of the author. Cooperas the author questions the ideas brought by the immigrants on the Indian land. Forhim, modernization can only be enjoyed by the upper class of the society—the White.It cannot meet the necessity of the people native the Indians. They lose some benefitsbecause of the settlement of the immigrants in their land.